Research Handbook on the Sociology of the Family - Schneider, Norbert F. (Research Handbooks in Sociology series, 2021)
Exploring how family life has radically changed in recent decades, this comprehensive Research Handbook tracks the latest developments and trends in scholarly work on the family. With a particular focus on the European context, it addresses current debates and offers insights into key topics including: the division of housework, family forms and living arrangements, intergenerational relationships, partner choice, divorce and fertility behaviour.